2002
DOI: 10.1046/j.1445-2197.2002.02403.x
|View full text |Cite
|
Sign up to set email alerts
|

Postdischarge clean wound infections: Incidence underestimated and risk factors overemphasized

Abstract: The overall wound-infection rate is higher than previously described with two thirds of infections occurring after discharge. While inpatient wound-infection rates fit known risk factors, postdischarge wound-infection rates do not. Certain clean-wound operations have a higher incidence of infection than others. Consideration needs to be given to the identification of risk factors for postdischarge wound infections,and to further trials of prophylactic antibiotics in clean surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
26
0
4

Year Published

2005
2005
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(33 citation statements)
references
References 31 publications
(29 reference statements)
1
26
0
4
Order By: Relevance
“…14 It consideration of the existing international literature and the 2-13% rate of post-operative infection specified in the report from the 'National Strategy to Address Health Care Associated Infections', it appears that post-operative infection rates in podiatric surgery are relatively low. 9,16 …”
Section: Introductionmentioning
confidence: 99%
“…14 It consideration of the existing international literature and the 2-13% rate of post-operative infection specified in the report from the 'National Strategy to Address Health Care Associated Infections', it appears that post-operative infection rates in podiatric surgery are relatively low. 9,16 …”
Section: Introductionmentioning
confidence: 99%
“…It is known that since the beginning of the surgical treatment of myocardial ischemia for almost four decades, such procedure has become, alone, one of the most performed and studied procedures in the contemporary history of surgery [2,3]. Even with the use of arterial grafts, the saphenous vein is still the most used conduit, and complications that occur in the operated limb have been underestimated and has not been properly studied and developed [4][5][6].…”
Section: Introductionmentioning
confidence: 99%
“…JY Bhatia, et al [15] demonstrated high rate of incidence rate of WI in patients underwent CABG as (18.86%). Kay AE [13] and Omran AS, et al [14] found that incidence of WI was 24.4%. This dissimilarity was due to differences in the sample size of the present study.…”
Section: Discussionmentioning
confidence: 97%